Birth-related retinal hemorrhages: The Soonchunhyang University Cheonan Hospital universal newborn eye screening (SUCH-NES) study. - In Hwan Cho (Public Library of Science (PLoS), 2021)
Purpose To report the prevalence, related factors, and characteristics of birth-related retinal hemorrhages (RHs) according to their severity in healthy newborns using a telemedicine network and wide-field digital retinal imaging (WFDRI). Methods Newborns who underwent WFDRI at 61 obstetrics/gynecology hospitals between January 2017 and December 2019 were enrolled. Demographics and related factors were compared among newborns with and without RHs. The newborns' eyes were divided into the minimal, mild, moderate, and severe groups according to the number of RHs, and characteristics like bilaterality, laterality, involved retinal layer, involved zone, macular and/or optic nerve (ON) involvement were compared. Results Among 56247 newborns, 13026 had birth-related RHs (23.2%). Normal spontaneous vaginal delivery (NSVD) showed the highest association with RHs (odds ratio, 19.774; 95% confidence interval, 18.277-21.393; P < 0.001) on multivariate analysis. Bilateral RHs (8414/13026; 64.59%) were more common than unilateral RHs (4612/13026; 35.41%); however, unilateral RHs (2383/4217; 56.51%) were more common than bilateral RHs (1834/4217; 43.49%) in the minimal group. RHs showed no laterality differences between the two eyes (P = 0.493). Most RHs were intraretinal (18678/21440; 87.12%), and 2328 (31.65%) eyes with preretinal hemorrhage were observed in the severe group. Zone I RHs were common in the minimal (7072/7090; 99.75%), mild (4953/4960; 99.86%), and moderate (2013/2035; 98.92%) groups; zone I and II RHs were common in the severe group (4843/7355; 65.85%); and RHs in zone III were rare (7/21440; 0.03%). Most RHs showed no macular and/or ON involvement in the minimal and mild group; however, this was common in the severe group (7111/7355; 96.68%). Conclusions Birth-related RHs were common in healthy newborns and were significantly associated with NSVD. RHs were usually bilateral, intraretinal, and distributed posterior to the retina, but severe RHs had unique characteristics. Future long-term and longitudinal studies are required to elucidate the prognosis of severe RHs.